Synthesis and Characterization of Hybrid-Magnetic Nanoparticles and Their Application for Removal of Arsenic from Groundwater - Marta A. Bavio; Adriana G. Lista (The Scientific World Journal)
Multiwall carbon nanotubes (MWCNTs) were oxidized with different agents and a characterization study was carried out. Then, hybrid-magnetic nanoparticles (HMNPs) were synthesized as iron oxide supported on the selected multiwalled carbon nanotubes (MWCNTs-Fe3O4) obtained from MWCNTs oxidized with HNO3. The HMNPs characterization revealed the presence of iron oxide as magnetite onto the MWCNTs surfaces. These HMNPs were used for arsenic removal from groundwater. The adsorption process variables were optimized (concentration of NPs, contact time, and pH), and these systems could remove 39.93 mg As/g adsorbent. Therefore, these nanoparticles appear as a good alternative for removing arsenic from water samples.